Utilizing Participatory Mapping and GIS to Examine the Activity Spaces of Homeless Youth. Issue 3 (24th May 2016) - Townley, Greg; Pearson, L; Lehrwyn, Josephine M.; Prophet, Nicole T.; Trauernicht, Mareike
Abstract: Although previous studies have informed our understanding of certain aspects of youth homelessness, few studies have critically examined the spatial and social environments utilized by youth as they navigate life on the streets. This study employed participatory mapping and Geographic Information Systems (GIS) to examine the activity spaces of homeless youth as they relate to sense of community and psychological well‐being. Participants were 28 youth experiencing homelessness in Portland, Oregon, USA. Results suggest that youth engage most frequently in service‐related activities, and their activity participation is significantly associated with sense of community and psychological well‐being. The utility of innovative participatory methods for better understanding the diverse experiences of homeless youth is discussed alongside examination of their practical implications.